Citizens and Groups in Contemporary China - Falkenheim, Victor C. (Michigan Monographs In Chinese Studies, 2020)
Citizens and Groups in Contemporary China began with two symposia held in 1977 and 1978. The first, a workshop on "The Pursuit of Interest in China," was held in August 1977 at the University of Michigan, and was organized by Michel Oksenberg and Richard Baum. It was supported by a grant from the Joint Committee on Contemporary China of the Social Science Research Council and the American Council of Learned Societies, using funds provided by the Andrew Mellon Foundation. Its principal goal was to use detailed case studies to explore the relevance of interest group approaches to the study of Chinese politics. The second, a panel organized by the editor for the 1978 Chicago meeting of the Association of Asian Studies, sought to apply participatory approaches to the role of social groups in the Chinese political process. The striking degree of overlap in the focus, methodology, and participants in both meetings suggested to a number of the paper writers that there was a need for a more eclectic approach which would focus simultaneously on individual and group actors. The recognition that a volume based on such an approach might serve the needs of students and scholars seeking to examine the dynamics of informal influence and power in China was the stimulus for publishing the studies presented here in book form. [ix]